2015
DOI: 10.17719/jisr.20153813679
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Social Work Students towards the Ageism

Abstract: Ageism which is a concept first used in 1969 by Robert Butler, the first director of the National Institute on Aging, can be defined as "a process of systematic stereotyping and discrimination against people because they are old" (Butler, 1995: 35).Turkey's population is growing older and the elderly constitutes an important target group especially in terms of the social work profession. Therefore determining the causes of discriminatory attitudes towards the elderly is extremely important in terms of quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
6
1
Order By: Relevance
“…Although in this study no significant relationship was found between age or class of students and ageism attitude scores, Daba and Kesen (2015) and Köse et al(2015) found that older aged and senior class students were more likely to have lower ageism attitude scores. On the other hand, while Hweidi and Al-Obeistat (2006) and Turan et al (2016) reported that first year students had more favorable attitudes than senior students.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…Although in this study no significant relationship was found between age or class of students and ageism attitude scores, Daba and Kesen (2015) and Köse et al(2015) found that older aged and senior class students were more likely to have lower ageism attitude scores. On the other hand, while Hweidi and Al-Obeistat (2006) and Turan et al (2016) reported that first year students had more favorable attitudes than senior students.…”
Section: Discussioncontrasting
confidence: 76%
“…Other previous research has found that age or studying class play a role in positive ageism scores (Daba & Kesen ,2015;Köse et al, 2015;Hweidi & Al-Obesitat, 2006 ;Hughes et al, 2008;Kızılcı et al, 2013, ;Kulakçı, 2010). Soyuer et al (2010), Bleijenberg et al (2012), Özdemir and Bilgili (2016) and Yılmaz and İnce (2017) reported that age and study year affect ageism scores of students.…”
Section: Literature Review and Research Questionsmentioning
confidence: 88%
See 3 more Smart Citations